A systematic multicellular spheroids screening approach lead to the identification of antineoplastic activity in three different plant extracts from the Egyptian flora - Walid Fayad, Salwa M. El-Hallouty, May A. El-Manawaty, Marwa M. Mounier, Ahmed A. F. Soliman, Abeer A. Yousry, Ayman A. Farghaly, Maha A. Fahmy, Zeinab M. Hasasn, Stig Linder & , Khaled Mahmoud (Journal of Applied Pharmaceutical Science, 2017)
Developing natural products as potential antineoplastic drugs is a meticulous process involving both compound isolation and biological testing. Many studies are based on primary screening using tumor cell viability as the readout followed by compound isolation. We here present an approach which utilizes both 2-D and 3-D cultured of tumor cells for screening and immortalized human non-transformed cells for counter screening. This procedure increases the precision of identifying tumor-specific cytotoxic compounds with interesting pharmacological properties. Using this straight-forward approach, we screened 500 plant extracts from the Egyptian flora for anticancer activity. The primary screen on 2-D cultured cells yielded 41 hits, 12 of which showed significant cytotoxicity on 3-D cultured cells. Of these, 4 extracts showed limited cytoxicity to normal cells. We conclude that only ~10% of the cytotoxic extracts showed desired properties with regard to tumor parenchyme penetration and tumor-specific activity. Extracts from Euphorbia dendroides L. herb, Ononis vaginalis Vahl. herb and Quercus robur L. branches were found to induce tumor apoptosis and were considered the most promising. These three extracts showed significant inhibition in the Ehrlich ascites carcinoma in vivo model and did not show severe toxicity on healthy animals.
Keywords: Anticancer, Plant extracts, Multicellular spheroids, Screening, Pro-apoptotic, Therapeutic window.